Experimental and Simulation Studies on the Warpage of Coreless Substrate Under Multiple Laminating Process - Hu, Zengming; Fan, Guowei; Xu, Jie; Fang, Zeming; Tang, Junqi; Luo, Li; Rong, Qianping; Liu, Qianfa; Liu, Dashun; Lu, Dong; Xue, Ke; Wang, Ke (Journal of Composites and Biodegradable Polymers, 2025)
Substrate warpage caused by curing process and thermal cycling is a very important issue in electronic packaging. Considerable efforts have been made to develop methods for predicting, measuring and controlling warpage. The current work focuses on the warpage and stress distribution of coreless substrates during multiple laminating process. Flexural property tests and thermal-mechanical measurements were carried out with samples cured under different lamination cycles in order to investigate the influence of in-plane anisotropic properties on the warpage. The results show that, with the increase of lamination cycles, both flexural modulus and coefficient of thermal expansion (CTE) of the laminates increase. Further, the cure shrinkage of the prepreg during curing, the effects of cure cycles and copper residuals on substrate warpage were examined through finite element analysis. The simulation results show that, after undergoing multiple curing processes, the thermoelastic parameters of the prepreg exhibit a complex relationship with the warpage and stress distribution of the substrate. Due to the increase in the number of material layers, the overall rigidity of the substrate is enhanced, and the average internal stress in the substrate structure decreases. This results in a downward trend in substrate warpage during multiple lamination processes. Based on the Finite Element Method (FEM) simulation results for the multiple laminating process, some modifications can be made regarding the substrate design and material selection, to optimize fabrication process of coreless substrate.